2011
DOI: 10.1007/s10096-011-1381-0
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of consecutive biomarkers measurement in the management of community-acquired pneumonia

Abstract: The aim of this study was to investigate whether procalcitonin (PCT), neopterin, C-reactive protein (CRP), and mid regional pro-atrial natriuretic peptide (MR-proANP) levels at admission and during the clinical course can be useful for the management of patients with pneumonia. The study population consisted of 75 patients with clinical and radiological diagnosis of pneumonia. Serum samples were collected at admission and during hospitalization. Complications were defined as intensive care unit (ICU) admission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 49 publications
4
29
0
6
Order By: Relevance
“…Other studies have shown that neopterin is a non-specific biomarker which its level also elevated in other conditions such as cardiovascular disease, pneumonia and colorectal cancer [20][21][22]. Hence, this could possibly explain the failure to differentiate between non-dengue fever and dengue without warning signs in our study.…”
Section: Discussionmentioning
confidence: 71%
“…Other studies have shown that neopterin is a non-specific biomarker which its level also elevated in other conditions such as cardiovascular disease, pneumonia and colorectal cancer [20][21][22]. Hence, this could possibly explain the failure to differentiate between non-dengue fever and dengue without warning signs in our study.…”
Section: Discussionmentioning
confidence: 71%
“…Judicious use of procalcitonin to assess CAP severity and to shorten duration of antibiotic therapy, is probably best way forwards in limiting multidrug resistant pathogens [42][43][44][45][46][47][48].…”
Section: Antimicrobial Therapymentioning
confidence: 99%
“…Однако типичный для ВП у лиц молодого возраста лейкоцитоз не всегда регистриру ется у пожилых пациентов. Так, E.Joffe et al на осно вании результатов исследования, посвященного дифференициальной диагностике ВП и острой де компенсации ХСН у данной возрастной категории, несмотря на достоверность различий, не рекоменду ется использование искомого показателя в клини ческой практике вследствие значительной его вари абельности в обеих группах ( [103]. Данный биомаркер может использо ваться для оптимизации режима системной АБТ, а также с целью дифференциальной диагностики ВП и декомпенсации ХСН [100,107].…”
Section: лабораторная диагностикаunclassified
“…При этом уровень прокальцитонина сыворотки крови не только коррелирует с тяжестью течения заболева ния, но и может использоваться в качестве предик тора неблагоприятного прогноза ВП [34,82,103,105,108]. У лиц пожилого и старческого возраста с со путствующими заболеваниями средние значения исследуемого параметра при развитии ИНДП варьи руют: в исследовании A.…”
Section: лабораторная диагностикаunclassified
See 1 more Smart Citation